Build towns instead of camps: Uganda as an example of integrative refugee policy - Merle Kreibaum (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
The public perception of the situation of refugees differs from the facts in two key aspects: the overwhelming majority of refugees stay in poor neighbouring countries adjoining their place of origin (86 percent) and they stay there a very long time (17 years on average). Although this has been known for a considerable time, these host countries frequently receive no support and refugees have scarcely any opportunity to establish themselves permanently and integrate into their host communities. As a consequence, thought is increasingly being paid to replacing the typical refugee camps - which are primarily designed for the provision of emergency support for refugees – with longer term approaches in refugee policy. One example of a successfully integrative refugee policy – and therefore a possible role model for other countries – is that of Uganda. Since 1999 the Ugandan government has pursued an approach of local social and economic integration of refugees. They receive land, are permitted to work and are thus intended to become independent of assistance. This liberal policy is also of benefit to the native population: the enhanced economic dynamic in areas in which many refugees live leads to higher consumption and improved access to public infrastructure for people in neighbouring villages. In particular, they are also able to use the schools and health clinics operated by the aid organisations. However, the subjective perception of the local population does not reflect these positive developments: they view their economic situation as poorer than people in other areas of Uganda. Local conflicts over land flare up frequently and there are indications that the Ugandan government spends less on the operation of health clinics and the support of poor people in districts with a high refugee presence. Although the government and the aid organisations strive to ensure that none of the groups is worse off than the other and to dismantle prejudices through encounters, the (perceived) competition for resources endures. The Ugandan experiences and challenges in the support of refugees in Kenya and Jordan underscore the major potential of an integrative refugee policy. The local population can benefit from this and costs are saved in the support of refugees. Four recommendations can be drawn from the analysis for host countries that house large numbers of refugees: Building settlements instead of camps and giving refugees the right to work results in an economic dynamism that also benefits the local population in the region. This requires good co-ordination between national government and international donors, for example with regard to public services and the allocation of funding. To avoid conflicts between refugees and the local population, it is advisable to inform the native citizens of the advantages and encourage interaction between the two groups. Particular consideration should be given to poor population groups, who should not be disadvantaged by the presence of the refugees. Aid payments should be considered where appropriate.
Keywords: 330; Soziale Sicherung und Inklusion; Sicherheit; Frieden und fragile Staaten